Księdza Tischnera mocowanie się ze słowem. Wokół Kazań starosądeckich - Witold Ostafiński (Polonia Sacra)
Seeking the proper language for preaching was Fr. Tischner’s greatest pastoral challenge. In the simplicity of thought and language he expressed his respect for the recipient, whom he managed to charm with the word. He offered, but did not impose, his point of view upon recipients, and examined the word of God together with the audience. With his straightforward and fluent narration he invited his audience to enter the space of dialogue. The choice of linguistic measures makes the texts of sermons communicative, coherent, logical, orderly, carefully thought out in terms of invention, disposition and allocution. The speaker impresses us with his consequence, the discipline of speech, he avoids theological phrasings, uses the language devoid of pathos, overblown style, exaltation. Kazania starosądeckie (Starosądeckie sermons) combine wit and wisdom, philosophy and life.